2011
DOI: 10.1124/mol.110.068528
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL Is a Dominant Antiapoptotic Protein that Inhibits Homoharringtonine-Induced Apoptosis in Leukemia Cells

Abstract: Homoharringtonine (HHT) has been reported to be effective in a portion of patients with acute myeloid leukemia (AML) or chronic myeloid leukemia (CML). To investigate its mechanism of action, cell growth inhibition and cytotoxicity of HHT were investigated in three AML cell lines, HL-60, NB4, and U937, and in three CML cell lines, K562, KU812, and KCL22. AML cells were more sensitive than CML cells to HHT-induced cytotoxicity. Using HL-60 cells, it was revealed that HHT decreased the levels of myeloid cell leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…SiRNA targeting X-linked inhibitor of apoptosis protein (XIAP) and negative control siRNA (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA) were used as previously described (12). Cells grown to ~60% confluence in 6-well plates were transfected with 50 pmol siRNA mixed with LipoTrust Ex Oligo reagent (Hokkaido System Science Co., Ltd., Hokkaido, Japan) for 48 h in serum-free medium.…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…SiRNA targeting X-linked inhibitor of apoptosis protein (XIAP) and negative control siRNA (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA) were used as previously described (12). Cells grown to ~60% confluence in 6-well plates were transfected with 50 pmol siRNA mixed with LipoTrust Ex Oligo reagent (Hokkaido System Science Co., Ltd., Hokkaido, Japan) for 48 h in serum-free medium.…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…The activation of caspase-9 is controlled by the antiapoptotic proteins Bcl-2, Bcl-xL, and Mcl-1 by maintaining MTP (19). Bcl-xL is not expressed in HL-60 cells (20). The levels of Bcl-2 and Mcl-1 proteins in both HL-60 and HP100-1 cells after treatments with either 6s or 6u were compared and it was found that Mcl-1 levels, but not those of Bcl-2, were decreased in both cell lines (Fig.…”
Section: S and 6u Induce Apoptosis In Hl-60 Cells Through Caspase Acmentioning
confidence: 99%
“…Previously, HHT has been revealed to induce apoptosis in various types of leukemic cells, which was characterized by cytochrome c release and activation of caspase (30). In AML cells, HHT leads to a decrease in mitochondrial membrane potential (31), which is regulated by activation of caspase-9 via cleaved Bid as a result of caspase-8 activation. In the present study, enhanced activation of caspase-9 and increased release of cytochrome c were observed, and may have been the result of enhanced activation of the extrinsic apoptosis pathway induced by upregulation of TRAIL and DR4/DR5.…”
mentioning
confidence: 99%